(untitled) (Research, Society and Development, 2025)
The management of patients with suspected or confirmed Brain Death (BD) in the Intensive Care Unit (ICU) represents a scenario of technical, ethical, and emotional complexity for the nursing team. The aim of this study was to synthesize scientific evidence addressing the challenges faced by nursing professionals in managing patients with suspected brain death in the intensive care setting. This is an Integrative Literature Review based on searches conducted in SciELO, BVS, Google Scholar, Lilacs, and PubMed databases, covering publications in Portuguese from 2018 to 2025. The descriptors used were “brain death,” “nursing care,” and “intensive care unit.” The results reveal that nurses play a central and dual role: they must ensure rigorous hemodynamic, fluid, and temperature control to maintain organ viability (potential donors). At the same time, the greatest challenges lie in the human dimension, involving emotional overload, difficulty dealing with the life-death dichotomy, and effective communication with families. It is concluded that improving care quality requires investment in continuing education to enhance both technical-scientific proficiency in maintenance protocols and interpersonal communication and family support skills, aiming to ensure patient dignity and optimize the organ donation process.